Effect of dentin roughness on the adhesive performance in non-carious cervical lesions: A double-blind randomized clinical trial. (February 2018) - Loguercio, Alessandro D.; Luque-Martinez, Issis Virginia; Fuentes, Sebastian; Reis, Alessandra; Muñoz, Miguel Angel
Abstract: Objective: This double-blind randomized clinical trial evaluates the influence of dentin roughening (RO) on the clinical behavior of a new universal multi-mode adhesive (Tetric N-Bond Universal; Ivoclar-Vivadent) applied as self-etch and as etch-and-rinse in non-carious cervical lesions (NCCLs). Methods: A total of 192 restorations were randomly placed in 48 patients according to the following groups: ER – Etch-and-rinse (no preparation); SE – self-etch (no preparation); ER + RO and; SE + RO. The resin composite Empress Direct (Ivoclar-Vivadent) was placed incrementally. The restorations were evaluated after one week (baseline), 6 and 18 months, using the FDI and USPHS criteria. Statistical analyses were performed using appropriate tests (α = 0.05). Results: Fifteen restorations were lost at 18 months (3 for SE, 2 for ER, 5 for SE + RO and 5 for ER + RO) (p > 0.05 between groups). Post-operative sensitivity wasn't observed in any of the recall periods. Eighty-four restorations were considered to have minor discrepancies in marginal adaptation at the 18-month recall using the FDI criteria (24 for SE, 18 for ER, 22 for SE + RO and 20 for ER + RO; p > 0.05 between groups). Nineteen restorations were considered to have minor discrepancies in marginal discoloration at the 18-month recall (10 for SE, 03 for ER, 05 for SE + RO and 01 for ER + RO; p > 0.05 between groups). Conclusion: The dentin roughening before application of Tetric N-Bond Universal as self-etch and etch-and-rinse didn't affect the clinical behavior of composite restorations placed in NCCLs.